Influence of Implementation of Health Protocol and Quality of Service on Guest Loyalty Stay at Martin Anugrah Hotel, Dolok Sanggul District in Humbang Hasundutan Regency (New Normal Pandemi/Covid-19 Study) - M.Hirsan Hanafi (Politeknik Pariwisata Medan, 2021)
The new normal, of course, requires certain attitudes and behaviors from all parties so that the goals of the concept can be realized. In other words, these attitudes and behaviors, as reflected in the notion of the new normal, indicate that the cultural aspect of society in preventing the transmission of the virus plays a central role. Service quality is how far the difference between the reality and the expectations of customers for the services they receive. However, today's organizations recognize that profitability can be achieved more by retaining existing customers, and keeping them loyal to the company rather than trying to acquire new customers. This research was carried out with an approach by emphasizing theory testing and measuring variables with numbers by analyzing data using statistical procedures using multiple regression analysis. The dependent variable in this study is the implementation of health protocols and service quality, while the independent variable is the Lotality of Staying Guests. The formulation of the problem in this study are: a. How does the application of health protocols affect guest loyalty? b. How does service quality affect guest loyalty? c. How does the simultaneous application of health protocols and service quality affect guest loyalty? Based on the results of the study, it was concluded that there was a positive and significant effect between the implementation of the Health Protocol (X1) on the Loyalty of Guests Staying at the Martin Anugrah Hotel, Dolok Sanggul District, Humbang Hasundutan Regency (Y). There is a positive and significant effect between Service Quality (X2) on Loyalty of Guests Staying at Martin Anugrah Hotel, Dolok Sanggul District, Humbang Hasundutan Regency (Y). Simultaneously (F test) with a value of sig < 0.000, it can be concluded that the application of the Health Protocol (X1) and Service Quality (X2) has a positive effect on the loyalty of guests staying at the Martin Anugrah Hotel, Dolok Sanggul District, Humbang Hasundutan Regency (Y). The suggestions in the results of this study should be that the management of Hotel Martin Anugrah remains consistent and never stops in implementing health protocols and continues to improve the quality of service to guests so that loyal guests will continue to believe in their minds that the hotel business is very healthy and indeed worth a visit. always due to full attention to each guest.